Insecure attachment predicts ambivalent social threat and reward perceptions in romantic relationships. (August 2013) - MacDonald, Geoff; Locke, Kenneth D.; Spielmann, Stephanie S.; Joel, Samantha
Although theoretical perspectives on adult attachment forward relational ambivalence as a defining characteristic of at least some forms of insecurity, work demonstrating an ambivalent structure to the relational attitudes of insecure individuals has been rare. The current research examines the similarity and intensity of perceptions of social threat (i.e., concerns over rejection) and social reward (i.e., opportunities for intimacy) in romantic relationships. Using a sample of 1004 participants, evidence for relational ambivalence was found for both anxious and avoidant attachment. Individuals high in anxious attachment reported relatively similar and intense threat and reward perceptions, whereas individuals high in avoidant attachment showed evidence of similar, but not intense, threat and reward perceptions. Thus, the weighing of prospects for rejection and intimacy in romantic relationships arguably leads to what researchers traditionally think of as ambivalence for those high in attachment anxiety, but something more akin to indifference for those high in attachment avoidance. More broadly, this work provides a set of tools and methods for carefully examining ambivalence in close relationships.